Regional population structure and young workers’ wages - Garloff, Alfred Alexander; Roth, Duncan (Marburg, 2017)
"This paper estimates the effect that changes in the size of the youth population have on the wages of young workers. Assuming that differently aged workers are only imperfectly substitutable, economic theory predicts that individuals in larger age groups earn lower wages. We test this hypothesis for a sample of young, male, full-time employees in Western Germany during the period 1999-2010. In contrast to other studies, functional rather than administrative spatial entities are used as they provide a more accurate measure of the youth population in an actual labour market. Based on instrumental variables estimation, we show that an increase in the youth share by one percentage point is predicted to decrease a young worker’s wages by 3%. Our results also suggest that a substantial part of this effect is due to members of larger age groups being more likely to be employed in lower-paying occupations."